Stratafikasi Sosial dan Korelasinya Dengan Perilaku Hukum - Muhammad Yusuf (Siyasah Wa Qanuniyah, 2024)
This research takes the title "The relationship between social strata and legal behavior". This research was conducted qualitatively using library research and data sources from secondary sources using primary materials. The results of this research conclude that there have been many rather surprising events related to lawenforcement (sanctions) imposed on classes of society who occupy positions withpeople who do not occupy positions at all, in fact there is an opinion circulatingin the community that "the law is blunt up but sharp down". This argument isrepresentative of the community's argument against the ineffective legalassessment of the community against the current law. In its embodiment, the lawcan increase or decrease. A complaint made to the police is a legal event whencompared to a police station where there are no complaints made by the public atall. Quantitatively, there will be more legal proceedings if the frequency oflawsuits in a district court becomes high or there is an increase. An official who istemporarily carrying out his duties is not subject to a temporary examination untilhis term of office ends. The problem of law enforcement that is oriented to social status is what often becomes a problem like this which in the application of law often ca uses the cause of not achieving legal goals, namely justice, especiallyjustice in a substantive manner.